The development of a standardised protocol for monitoring heart rate recovery in soccer players - Orme, P.; Anderson, L.; Morgans, R.; Morton, J. P.; Drust, B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Physiological monitoring during the recovery process following elite soccer performance has been an area of considerable interest over recent years. The aim of this study was to develop a standardised exercise protocol for use in the calculation of heart rate recovery (HRR) that can be integrated into a training strategy used by an elite team. Furthermore, this study attempted to evaluate the reliability of the HR response to the protocol as well as compare the protocol to specific physical loads completed during the recovery period following soccer match play. Methods: Three exercise protocols (1-6x60m 6ms 10:20s; 2-6x80m 5ms 16:14s; 3-6x60m 5ms 12:8s) were tested for reliability of HR response and suitability with regards to soccer training loads. Nine male competitive soccer players (Mean±SD: age 17±0.6 years, height 1.7±0.9m, body mass: 63±9.0kg) took part in the study. All subjects completed one trail of each protocol on each of 5 data collection days (3 familiarisation trials and 2 testing sessions). Trials completed on each data collection day were separated by 30 min of seated rest. HR and GPS data was collected throughout all trials (duration, total distance, peak speed, %MAXHR, HRR at 1 min post exercise). Data were analysed using standard error of measurement (SEM) and coefficient of variation (CV) for reliability assessment and by the use of paired t-tests to compare the physical loads completed in the protocol and by players during actual recovery training sessions. Results: There were no significant differences (P<0.05) between previous soccer recovery activities completed in training (duration- 3min, distance- 399m, peak speed- 4.7ms, %MAXHR- 74%) and the exercise protocols developed in this study (duration- 4min, distance- 406m, peak speed- 5.3ms, %MAXHR- 86%). All protocols elicited a %MAXHR above 80% (protocol 1-82.5%, protocol 2-85.5%, protocol 3-89.5%). CV and SEM were lower for both HRR and %MAXHR for protocol 2 (HRR CV=9.95%, HRR SEM=2.14% - %MAXHR CV=2.57%, %MAXHR SEM=2.19%) compared with protocol 1 (HRR CV=21.99%, HRR SEM=5.74% - %MAXHR CV=4.08%, %MAXHR SEM=3.36%) and 3 (HRR CV=40.41%, HRR SEM=10.41% - %MAXHR CV=2.62%, %MAXHR SEM=2.33%). Discussion: This study developed a protocol (6x80m 5ms, 16:14s) that is suitable for use as a real world monitoring tool during the recovery period following soccer match play. The developed protocol presented CV and SEM data to suggest that this protocol is suitable for use to detect changes in the HR response.